IMPLEMENTASI PROGRAM JAMINAN SOSIAL KETENAGAKERJAAN PADA PENGEMUDI OJEK ONLINE DI KOTA PEKANBARU - Monica Oktriani Gurusinga; Sujianto Sujianto (Cross-border, 2023)
The employment social security program is a program created by the government through the Social Security Organizing Agency (BPJS) employment which aims to protect workers and help development and the economy. This research focuses on non-wage earners, especially online motorcycle taxi (ojol) drivers because of their status as partners so that employers are not responsible for BPJS Employment from ojol drivers, then also the high mobility of ojol drivers so that they are prone to accidents. Meanwhile, from the data from BPJS Employment Pekanbaru Panam branch, the number of ojol driver participants is still very low. The purpose of this study is to describe and identify the implementation and inhibiting factors of the employment social security program on ojol drivers in Pekanbaru City. The research method used is qualitative research that is descriptive and uses the theory of George Edward III which has 4 variables that influence the success of policy implementation, namely communication, resources, dispositions, and bureaucratic structure. The results of the study found that the implementation of the program was not optimal enough because obstacles were still found. This is evidenced by the low low level of knowledge of the target group about program, lack of implementor commitment, and convoluted bureaucracy